Future Horizons Canadian Digital Humanities - Barrett, Paul; Roger, Sarah (Canadian Literature Collection, 2023)
Future Horizons examines how digital humanities transform conceptions of the humanities in Canadian contexts. It connects thematic concerns with individual techniques, scholarly investigations with artistic interventions; it meditates on past successes and proposes potential areas for improvement.